K65R and K65A substitutions in HIV-1 reverse transcriptase enhance polymerase fidelity by decreasing both dNTP misinsertion and mispaired primer extension efficiencies - Garforth, Scott J. (2010)
The Lys65 residue, in the fingers domain of HIV reverse transcriptase (RT), interacts in a sequence independent fashion with the incoming dNTP. Previously, we showed that a 5 amino acid deletion spanning Lys65 and a K65A substitution both enhanced the fidelity of dNTP insertion. We hypothesized that the Lys65 residue enhances dNTP misinsertion via interactions with the γ-phosphate of the incoming dNTP. We now examine this hypothesis in pre-steady state kinetic studies using wild type HIV-1 RT and two substitution mutants: K65A and K65R. The K65R mutation did not greatly increase misinsertion fidelity, but the K65A mutation led to higher incorporation fidelity. For a misinsertion to become a permanent error, it needs to be accompanied by the extension of the mispaired terminus thus formed. Both mutants, and the wild-type enzyme, discriminated against the mismatched primer at the catalytic step (k(pol)). Additionally, K65A and K65R mutants displayed a further decrease in mismatch extension efficiency, primarily at the level of dNTP binding. We employed hydroxyl radical footprinting to determine the position of the RT on the primer-template. The wild-type and Lys65 substituted enzymes occupied the same position at the primer terminus; the presence of a mismatched primer terminus caused all three enzymes to be displaced to a −2 position relative to the primer 3’ end. In the context of an efficiently extended mismatched terminus, the presence of the next complementary nucleotide overcame the displacement, resulting in a complex resembling the matched terminus. The results are consistent with the observed reduction in k(pol) in mispaired primer extension being due to the position of the enzyme at a mismatched terminus. Our work shows the influence of stabilizing interactions of Lys65 with the incoming dNTP in affecting two different aspects of polymerase fidelity.